2003
DOI: 10.1136/gut.52.11.1572
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fructo-oligosaccharides and lactulose inhibit intestinal colonisation but stimulate translocation of salmonella in rats

Abstract: Background and aims: It is frequently assumed that dietary non-digestible carbohydrates improve host resistance to intestinal infections by stimulating the protective gut microflora. However, compelling scientific evidence from in vivo infection studies is lacking. Therefore, we studied the effect of several nondigestible carbohydrates on the resistance of rats to Salmonella enteritidis infection. Methods: Rats (n = 8 per group) were fed ''humanised'' purified diets containing 4% lactulose, fructooligosacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 51 publications
6
101
2
Order By: Relevance
“…Epithelial colonic permeability assessed in Ussing chambers was not different amongst groups although ZO1 mRNA expression was reduced by 40 % in the supplemented group compared with the non-supplemented (87) . A similar galactooligosaccharides-induced increase in bacterial translocation has already been observed in adults (88,89) but whether such a phenomenon in the neonate could be beneficial or not for the maturation of the immune system has not been determined.…”
Section: Prebioticsmentioning
confidence: 82%
“…Epithelial colonic permeability assessed in Ussing chambers was not different amongst groups although ZO1 mRNA expression was reduced by 40 % in the supplemented group compared with the non-supplemented (87) . A similar galactooligosaccharides-induced increase in bacterial translocation has already been observed in adults (88,89) but whether such a phenomenon in the neonate could be beneficial or not for the maturation of the immune system has not been determined.…”
Section: Prebioticsmentioning
confidence: 82%
“…As a matter of fact, an increased translocation of Salmonella toward spleen was reported in adult rats fed a low-calcium diet enriched with fructooligosaccharides or inulin when animals were infected with this pathogen (13,19). The authors hypothesized that the rapid fermentation of the prebiotics led to high ceco-colonic concentrations of organic acids that impaired the intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Such an impact could be considered as irrelevant since neonatal gut microbiota does not produce butyrate (12), and therefore prebiotic supplementation solely enhances lactate and acetate production in infants (2). Colonic perfusions of highly concentrated (300 mM) acetate, however, also causes mucosal damage in rat pups (10,11) and elevation of organic acid levels have been linked to the increased incidence of Salmonella translocation observed in adult rats fed a lowcalcium diet supplemented with prebiotics (13,14).…”
mentioning
confidence: 99%
“…This effect was counteracted by normalizing the calcium intake of the rats. 68,69 In contrast, Osman et al 70 showed a reduction of bacterial translocation to the liver in a dextran sulfate sodium (DSS)-induced colitis in rats fed oligofructose, whereas bacterial translocation was increased using a combination of oligofructose, inulin, and B. infantis DSM 15158. Mangell et al 71 showed that Lactobacillus plantarum 299v reduced bacterial translocation to liver and mesenteric lymph nodes in rats, whereas prebiotics (oatmeal) did not prevent this.…”
Section: Adverse Effects Of Prebioticsmentioning
confidence: 99%